Women in the hospitality industry: issues & challenges / Noorliza Zainol and Abdul Rahman Ahmad Rozali - Zainol, Noorliza; Ahmad Rozali, Abdul Rahman (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
The most successful and thriving sectors of hospitality industry is usually supported by female-centric employees. By the year 2019, there would be 275 million jobs offer in the hospitality sector projected to be filled mostly by women (the World Travel and Tourism Council, 2016). However, the existing gender discrimination becomes a very challenging environment for women employees. The aforesaid job opportunities are actually more focused towards male candidates, as they are viewed to be mentally accomplished and able to work for longer hours. The hotel industry is known for long working hours, overtime shifts, stressful and difficult to handle customers (Hsieh et a I., 2010). Hence, when a firm opens for promotions, the male candidates are often preferred to more quickly. Traditionally, women were considered as home-makers, caregiver for children and guardian for household. They are viewed neither capable to work for long hours nor shift-work where most find it difficult to stabilize between their work and personal life.